Rumiación: un trastorno sicosomático poco frecuente. Reporte de dos casos. - Amador, Manuel; Vega Vega, René; Razón, Roberto; Cid, Mireya; Marcolles, Carlos; Fariñas, Georgina (Revista Cubana de Pediatría, 2023)
Rumiación Digestiva